The Policy to Optimization of Social Media for Traffic Management in Islamic Perspectives - Rio Febriannur Rachman (Universitas Nahdlatul Ulama Surabaya, 2021)
This study discusses on how information and communication technology-based policies in the field of transportation was carried out by the Department of Transportation, City of Surabaya, through the Surabaya Intelligent Transport System or SITS program. This research used the theory of technological determination and public policy as the basis of thought. In addition, the concept of maqâsid syari'ah was also used to consider how the implementation of this policy, towards the benefit or welfare for the society, in an Islamic perspective was done. Descriptive qualitative method with literature review approach was used as a framework for formulating conclusions. Data collection was carried out through searching literature and other documents related to the topic. The results of this study indicated that the SITS policy of the Department of Transportation, City of Surabaya, was running well and had positive impact. This public policy which utilizes digital media was in line with the concept of maqâsid syari'ah.